Anatomical and chemical characterization of Alstonia boonei for pulp and paper production - Afrifah, Kojo Agyapong (Les (Ljubljana), 2021)
Alstonia boonei, an abundant lesser utilized species within the West African Subregion, was evaluated as an alternative raw material for pulp and paper production. The basic density (BD), fibre characteristics fibre length (FL), fibre diameter (FD), lumen diameter (LD) and wall thickness (WT), derived anatomical indices Flexibility Ratio (FR), Slenderness Ratio (SR), Rigidity Coefficient (RC), Luce’s Shape Factor (LSF), Solids Factor (SF) and Runkel Ratio (RR) and chemical composition (lignin, holocellulose, 1% NaOH solubility and ash contents) of A. boonei were studied to evaluate variation along the trunk (base, middle and top portions) and ascertain its suitability for pulp and paper production. Significant variations were observed in the density and fibre characteristics along the trunk of the tree. Although the FD was large, the observed adequate FL, thin-wall and large LD implied easy beating of fibres and manufacture of dense, smooth and strong papers. The favourable SF, RR, FR, RC, and LSF values obtained for the fibres would produce papers with suitable burst and tearing strengths and folding endurance. Chemically the lower lignin (< 30%), ash and 1% NaOH solubility and the high holocellulose contents of A. boonei, will generate a higher pulp yield. A. boonei although a low-density species, will be desirable for pulp and paper production
Keywords: Alstonia boonei; celuloza; characteristics; fibre; les; lesser utilized species; manj uporabljana lesna vrsta; paper; papir; pulp; wood; značilnosti vlaken